2016
DOI: 10.1002/bdra.23528
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trend in the reported birth prevalence of cleft lip and/or cleft palate in Brazil, 2000 to 2013

Abstract: In recent years, there appears to be an upward trend in the reported prevalence of CL/P in Brazil, confined to the less developed regions of the country. The increase likely reflects improved surveillance; whether it also reflects etiologic differences is unknown. Birth Defects Research (Part A) 106:789-792, 2016. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 15 publications
2
28
1
7
Order By: Relevance
“…The authors mentioned that this temporal trend of increasing prevalence of orofacial clefts, limited to the poorest regions of the country, may be attributed to changes in risk factors, as well as to the improvement of the record-taking process for this malformation in the SINASC. 15 Considering geographic regions individually, our study observed no consistency in the increase or decrease in the number of records between the years 2009 and 2013, except for the Southeast, which presented a steadily increasing trend. Taking into account the country as a whole, the authors of this study observed a slightly increasing trend in the period studied (Figure 2).…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…The authors mentioned that this temporal trend of increasing prevalence of orofacial clefts, limited to the poorest regions of the country, may be attributed to changes in risk factors, as well as to the improvement of the record-taking process for this malformation in the SINASC. 15 Considering geographic regions individually, our study observed no consistency in the increase or decrease in the number of records between the years 2009 and 2013, except for the Southeast, which presented a steadily increasing trend. Taking into account the country as a whole, the authors of this study observed a slightly increasing trend in the period studied (Figure 2).…”
Section: Discussioncontrasting
confidence: 66%
“…Another study carried out later with data between 1998 and 2002 found a prevalence rate of 3.6 per 10,000 live births. 14 Recently, Abreu et al 15 reported an overall prevalence of 4.85 per 10,000 live births, up from 3.94 to 5.46 between 2000 and 2013. In this study, it was observed that this trend occurred mainly in the Northeast (4.7% per year), the North (3.3% per year) and the Center-West (2.9% per year).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of cleft was associated with prematurity, race/color white, children of mothers with age greater than or equal to 35 years old and worse conditions of vitality at birth. [12][13][14][15][16] The average rate of cleft lip and/or cleft palate was 0.51/1000 live births; corroborating an analysis carried out in the period from 2000 to 2013 that pointed to a national average of 0.48/1000 live births. 13 As regards the Brazilian regions most affected by this anomaly, the South and Southeast regions presented higher rates, a fact that is consistent with the literature, in which the higher prevalence of cleft lip and/or cleft palate in Brazil was verified in the South region, being the lowest rate corresponding to the northeast region.…”
Section: Discussionsupporting
confidence: 61%
“…This CP underreporting was described by Nunes et al () with data from cleft patients investigated at treatment centers in Campos dos Goytacazes, in Rio de Janeiro, Brazil and was different from that recorded in the SINASC database in the same period and for the same population. However, the pattern of the CLP‐deficient frequency that we observed has already been published with the SINASC data from Mato Grosso do Sul in 2003–2007 (Gardenal, Bastos, Pontes, & Bogo, ) and from Brazil in 2009–2013 (Sousa & Roncalli, ), and 2000–2013 (Abreu et al, ), although this issue was not thoroughly discussed. Thus, assuming that the combined CL and CLP represent 74% of clefts, as described by Loffredo, Freitas, and Grigolli () in Brazil, and considering that CP is more under‐reported than other types of clefts, it is likely that the high CLP under‐reporting observed in the SINASC data is the result of encoding issues rather than of deficiencies related to case ascertainment.…”
Section: Discussionmentioning
confidence: 63%